Visualization of CCTV coverage in public building space using BIM technology - Chen, Huan-Ting; Wu, Si-Wei; Hsieh, Shang-Hsien (Visualization in engineering, 2013)
Background Nowadays, the use of Closed Circuit Television (CCTV) systems is effective for monitoring traffic, preventing crime, and ensuring safety in many public spaces. However, the effectiveness of CCTV coverage is often achieved through design experience and trial-and-error, instead of being evaluated and visualized using a robust approach. Methods Firstly, a method for simulating varifocal CCTV lenses in order to attain different fields of view was developed, allowing real CCTV views to be approximated by adjusting the parametric properties of simulated CCTV cameras in the 3D BIM model. Secondly, an API (Application Programming Interface) plug-in program for a commercially available BIM tool was developed to facilitate the parametric modeling of CCTV systems and the evaluation of the CCTV coverage. Results A complete BIM model of an MRT (Mass Rapid Transit) station was chosen as a case study to apply the developed approach to the examination of CCTV coverage. Finally, the overall coverage of the CCTV systems for the MRT station were demonstrated visually and studied in the station's BIM model. Conclusions This research has developed a robust visualization approach for evaluating the coverage of CCTV systems in public building spaces. The developed approach is based on Building Information Modeling (BIM) technology and is capable of simulating CCTV systems in a 3D virtual environment in order to evaluate the CCTV coverage.